Common Grammatical Errors in Students’ Writing: A Qualitative Error-Analysis Study - Nur Hikmah; Sam Hermansyah; Jumiati Jumiati; Zulkifli N; Sri Rahayu; Nuraeni Syarif; Syamsuriani Syamsuriani (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This qualitative study investigates the common grammatical errors produced by English as a Foreign Language (EFL) students in written tasks, and explores possible underlying causes as reported by the students. Using an error-analysis framework, 60 undergraduate learners’ short essays were analyzed for grammatical errors; follow-up semi-structured interviews were conducted with 12 volunteers to probe students’ awareness and perceived causes. Findings indicate that article/determiner misuse, verb tense and aspect errors, subject-verb agreement, preposition misuse, and word order/sentence structure problems are among the most frequent error types. Interview data suggest that first-language transfer, inadequate exposure to grammatical input, faulty internalization of rules, and limited proofreading strategies contribute to recurring mistakes. Pedagogical implications include focused grammar instruction within writing contexts, increased corrective feedback that highlights patterns rather than isolated errors, and explicit metalinguistic awareness activities. The study contributes up-to-date qualitative evidence on error patterns and student perspectives to inform EFL writing pedagogy.